Mathematics

Evaluate the expression: a(b – c) if a = -6, b = 14, and c = 7


Answers

Riana

2 years ago Comment

-42 if i am correct because you always do the parentheses first then multiply -6.

Mayelinkay

2 years ago Comment

Here are the steps to figuring it out :) 

1. First, you have to plug in the values. So if a = -6, then you have to plug in -6 in the place of a in the problem. 
   -6 (14 - 7) <---- This is what the equation would look like after plugging in      the values. 
2. Now we always have to solve whatever is in the parentheses next.
    14 - 7 = 7 
3. After that, multiply -6 by 7
    -6 × 7 = -42

So -42 is your answer!

Hope I helped! <3